Existing and emerging uses of drones in restoration ecology. Issue 9 (26th June 2022) - Robinson, Jake M.; Harrison, Peter A.; Mavoa, Suzanne; Breed, Martin F.
Abstract: In the absence of effective and scalable human intervention, up to 95% of the world's ecosystems will be affected by anthropogenic degradation by 2050. Therefore, immediate and large‐scale ecological restoration is imperative to stem biodiversity loss and ecosystem decline. Ecologists must draw upon the most effective and efficient tools available to achieve successful restoration goals. Drones (i.e., unmanned aerial vehicles) are a valuable set of tools in the environmental, forestry, and agriculture sectors; however, there has been limited uptake in restoration ecology. Here, we aim to highlight the existing and emerging uses of drones in restoration science and practice. We discuss the strengths and weaknesses of these applications and provide a roadmap for increasing the utilisation of drones to refine and enhance restoration objectives. Our article is presented with the restoration continuum in mind, including sections for restoration planning, implementation and monitoring. We also take a novel approach by describing how drones relate to a globally recognised restoration tool published by the Society for Ecological Restoration . Drones are used in several restoration scenarios from mapping habitats and managing wildfires, to monitoring the effectiveness of restoration interventions. Many applications in other disciplines can also be transferred to restoration scenarios. However, the use of drones will be context‐dependent, and several technical and practical constraints need to be addressed. Drones have considerable potential to improve the science and practice of restoration at all stages of a restoration project, which is vital to realising the goals of the UN Decade on Ecosystem Restoration.